2021
DOI: 10.5194/dwes-2021-8
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predicting turbidity and Aluminum in drinking water treatment plants using Hybrid Network (GA- ANN) and GEP

Abstract: Abstract. Turbidity is the most important parameter needed to check the status of drinking water, as it is an integrated parameter because its high values indicate high values of other parameters related to water quality. Coagulation and flocculation are the most essential processes for the removal of turbidity in drinking water treatment plants. Using alum coagulants increases the aluminum residuals in treated water, which have been linked to Alzheimer's disease pathogenesis.In this paper, a hybrid algorithm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Ayanshola et al [8] utilized MLR and ANN models to predict treated water turbidity in a water treatment plant, achieving reasonable prediction accuracy with both methods. Alsaeed et al [9] developed prediction models for turbidity and aluminium in drinking water treatment plants using GA-ANN and GEP which can be used as early warning systems to provide information about water treatment plants. Godo-Pla et al [1] employed ANN to predict the oxidant demand in a full-scale drinking water treatment plant.…”
Section: Figure 3 Concentrations Of Manganese Iron and Ammonium In Ra...mentioning
confidence: 99%
See 1 more Smart Citation
“…Ayanshola et al [8] utilized MLR and ANN models to predict treated water turbidity in a water treatment plant, achieving reasonable prediction accuracy with both methods. Alsaeed et al [9] developed prediction models for turbidity and aluminium in drinking water treatment plants using GA-ANN and GEP which can be used as early warning systems to provide information about water treatment plants. Godo-Pla et al [1] employed ANN to predict the oxidant demand in a full-scale drinking water treatment plant.…”
Section: Figure 3 Concentrations Of Manganese Iron and Ammonium In Ra...mentioning
confidence: 99%
“…In research made by Kim and Parnichkun [7] prediction of settled water turbidity and optimal coagulant dosage in drinking water treatment plant was done using a hybrid model of kmeans clustering and adaptive neuro-fuzzy inference system. Use of multiple linear regression (MLR) and artificial neural network (ANN) models were used by Ayanshola et al [8] to predict treated water turbidity in a water treatment plant, while Alsaeed et al [9] have done prediction of turbidity and aluminium in drinking water treatment plants using hybrid network algorithm (GA-ANN) and gene expression method (GEP). ANN were used also by Godo-Pla et al [1] for predicting the oxidant demand in full-scale drinking water treatment plant.…”
Section: Introductionmentioning
confidence: 99%
“…ANN and other nonlinear model configurations have shown promise in several applications throughout the water treatment industry. Researchers have developed ANN models for cost optimization (Taloba, 2022), prediction of coagulant dose (Valentin and Denceux, 1999;Deveughèle and Do-Quang, 2004;Tahraoui et al, 2021;Lin et al, 2023), potassium permanganate dose requirements (Godo-Pla et al, 2019), source water quality (Hameed et al, 2023), sodium absorption in groundwater (Hasanpour Kashani et al, 2023), regional water demand (Zhang et al, 2019, and settled water turbidity (Wu and Lo, 2008;Al-baidhani and Alameedee, 2017;Kim and Parnichkun, 2017;Haghiri et al, 2018;Abba et al, 2020;Alsaeed et al, 2021;Ghasemi et al, 2022;Lin et al, 2023). Although several modeling techniques have been developed recently to predict coagulant dose based on source water quality, most of the work reported in literature either used bench-scale data (Haghiri et al, 2018) or lacked a sufficiently large data set (Albaidhani and Alameedee, 2017;Abba et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The ANN models were trained using the Levenberg-Marquardt algorithm, the research findings suggest that ANN's can accurately predict the optimal coagulant dosage, offering a promising approach to optimizing water treatment processes [1]. Prediction of turbidity and aluminium in drinking water treatment plants using Hybrid Network (GA-ANN) and GEP was done by Alsaeed et al (2021). The authors developed a hybrid network model combining genetic algorithms (GA) and artificial neural network (ANN) to predict turbidity and aluminium concentration in drinking water treatment plants.…”
Section: Introductionmentioning
confidence: 99%
“…The study utilized input variables such as raw water quality parameters, coagulant type and dosage, and treatment process variables to develop the hybrid GA-ANN model. The results showed that the hybrid model was effective in predicting turbidity and aluminium concentration, and the study suggested that the model could be used as a tool to optimize coagulant dosage and improve water treatment performance [2]. Kote et al (2019) have done modelling of chlorine and coagulant dose in a water treatment plant by artificial neural network.…”
Section: Introductionmentioning
confidence: 99%